Assessing the Impact of High Inflation on Organizational Performance in the Sri Lankan Manufacturing Sector During an Economic Crisis - Ratnamalala, Ratnamalala Bandaralage Dilshan Kavinda; Jílková, Petra; Fleischmann, Luboš, 1969-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This study aims to examine the effects of high inflation on financial performance of manufacturing companies in Sri Lanka during the recent economic crisis aggravated by COVID-19 pandemic. This research attempts to examine the relationships between inflation and three financial metrics: profitability, liquidity and solvency. The data related to the twenty publicly listed manufacturing firms, from 2014 to 2023, were collected using quantitative approach from their annual reports. Descriptive statistics, the correlation and regression techniques were employed in the analysis of data which reveals crucial findings. Inflation is shown to have a robust negative correlation with inflation and profitability, increasing costs ultimately reducing profits. Company size is found to be a moderating factor with larger firms having better financial resilience than smaller firms. Furthermore, this study establishes that inflation negatively impacts liquidity and solvency of manufacturing companies, necessitating this class of firms to compromise on meeting of short term and long-term financial obligations associated with debtors. Further on, the issue of exchange rate fluctuations, which also make profitability vulnerable – with the proper financial management strategies it is possible to overcome this problem. The insights of this research will be valuable for the stakeholders in the Sri Lankan manufacturing sector and provide insights into dynamics among inflation and financial performance in emerging markets. This study emphasizes how cost management and strategic financial planning play a critical role to firms confronting the uncertain economic environment, adaptation and resilience being essential to cope with it. By taking their entirety, the research provides action recommendations for policymakers and business leaders to bolster a manufacturing sector challenged by inflation.
Vedoucí práce: Petra Jílková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses